Glucagon like peptide 1 receptor agonists: therapy for diabetes management - Rojas, Natalia Andrea; Granados Vega, Elkyn Johan (CES Medicina, 2017)
Introduction: Glucagon-like peptide 1 agonists inhibit glucose-dependent glucagon secretion, decrease gastric emptying and appetite through neural mechanisms, contribute to glucose regulation and show reduction in glycated hemoglobin A. Methods: A bibliographic search was made on Medline® about pharmacology of the agonist glucagon-like peptide-1 receptor , Liraglutide, Lixisenatide, Albiglutide, Exenatide, Exenatide with long-acting release. Results: The GLP1 receptor agonist are agents involved with glycemic balance, weight loss induction and are associated with lower risk of hypoglycemia. They have shown efficacy in the treatment of hypoglycemia in patients with type-2 diabetes. Conclusions: GLP1 receptor agonist are part of the therapies for diabetes that have shown benefits in metabolic control, effectiveness in weight reduction and changes in glycated hemoglobin. More studies are needed to evaluate its long-term safety.